2015
DOI: 10.2147/ndt.s81482
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of high-intensity interval training on the mental and physical health of people with chronic schizophrenia

Abstract: BackgroundLow-volume high-intensity interval training (HIIT) is emerging as a time-efficient exercise strategy for improving cardiorespiratory fitness and for controlling blood sugar levels and hypertension. In addition, patient acceptance of HIIT may improve adherence to exercise programs. This study evaluated the effectiveness of HIIT for improving the mental and physical health of people with chronic schizophrenia.MethodsTwenty patients attending a psychiatric day care unit volunteered for an 8-week program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
1
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 34 publications
4
31
1
2
Order By: Relevance
“…diet, interpersonal encounter, environmental change) factors, which may, when taken together, help to explain the significant placebo rate in antipsychotic drug trials [1]. Exercise is one factor that has been shown to temporarily enhance treatment effects in schizophrenia [2][3][4][5][6][7][8]. Whether side effects are enhanced or dampened after exercise, however, has not been addressed in these studies.…”
mentioning
confidence: 99%
“…diet, interpersonal encounter, environmental change) factors, which may, when taken together, help to explain the significant placebo rate in antipsychotic drug trials [1]. Exercise is one factor that has been shown to temporarily enhance treatment effects in schizophrenia [2][3][4][5][6][7][8]. Whether side effects are enhanced or dampened after exercise, however, has not been addressed in these studies.…”
mentioning
confidence: 99%
“…Previous research into HIIT for adults with mental illness has focused on patients with a particular diagnosis (e.g. schizophrenia, depression, substance use) [296][297][298][299] . Understanding the feasibility and acceptability of different exercise approaches for heterogeneous patient groups may guide the implementation of exercise programs in mental health services, where patient groups are likely to be diverse.…”
Section: Discussionmentioning
confidence: 99%
“…One pre/post study with outpatients with schizophrenia used "body weight exercises" to achieve age-predicted heart rate ranges over eight weeks for three sessions/week, using a 4x3.75-minute circuit protocol 299 . That study discontinued participants who did not meet prescribed training intensities, and found that the program significantly improved depression, anxiety, and negative symptoms of schizophrenia 299 .…”
Section: Physical Activity Attitudes and Preferences Of Adults With Mmentioning
confidence: 99%
See 2 more Smart Citations